COMPARISON OF MACHINE LEARNING ALGORITHMS FOR PREDICTING MORTALITY FROM COVID-19 VIRUS - Дорошенко, Ірина; Кнігніцька, Тетяна; Дереторська, Тетяна (SWorldJournal, 2022)
The article compares the effectiveness of Machine Learning Algorithms on the example of Covid-19 distribution data. The following Machine Learning algorithms are considered: Logistic Regression, Support Vector Machine, Random Forest, K-Means. The accuracy